2017
DOI: 10.1103/physrevlett.119.207604
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Concurrence of Static and Dynamic Phenomena at the Morphotropic Phase Boundary of xBiNi0.5Zr0.5O3<

Abstract: We reveal that concurrent events of inherent entropy boosting and increased synchronization between A- and B-site cation vibrations of an ABO_{3}-type perovskite structure give rise to a larger piezoelectric response in a ferroelectric system at its morphotropic phase boundary (MPB). It is further evident that the superior piezoelectric properties of xBiNi_{0.5}Zr_{0.5}O_{3}-(1-x)PbTiO_{3} in comparison to xBiNi_{0.5}Ti_{0.5}O_{3}-(1-x)PbTiO_{3} are due to the absolute flattening of the local potentials for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…This view may also be emboldened by the fact that a related system (1-x)PbTiO3-(x)BiScO3 (PT-BS) shows clear evidence of rhombohedral distortion (the splitting of pseudo-cubic {111}pc Bragg profile into two) on the global scale on the BS excess side of the MPB region [5,21]. A recent neutron pair distribution function analysis of unpoled (1-x)PT-(x)BNZ by Datta et al [53] revealed a gradual change in the local structure from tetragonal to non-tetragonal with increasing composition (x). By comparing their results with those reported earlier for rhombohedral/monoclinic compositions of the PT-BS system [54], the authors argued in favour of the presence of MPB in PT-BNZ.…”
Section: Discussion the Non-mpb Nature Of Pt-bnzmentioning
confidence: 99%
“…This view may also be emboldened by the fact that a related system (1-x)PbTiO3-(x)BiScO3 (PT-BS) shows clear evidence of rhombohedral distortion (the splitting of pseudo-cubic {111}pc Bragg profile into two) on the global scale on the BS excess side of the MPB region [5,21]. A recent neutron pair distribution function analysis of unpoled (1-x)PT-(x)BNZ by Datta et al [53] revealed a gradual change in the local structure from tetragonal to non-tetragonal with increasing composition (x). By comparing their results with those reported earlier for rhombohedral/monoclinic compositions of the PT-BS system [54], the authors argued in favour of the presence of MPB in PT-BNZ.…”
Section: Discussion the Non-mpb Nature Of Pt-bnzmentioning
confidence: 99%
“…The x ‐dependencies of the mode wavenumbers indicate multistep composition‐induced transformations at room temperature: (a) the initial incorporation of BNiT ( x =0.1) increases the anisotropy of the A‐site local potentials by introducing a new lower‐energy state (Figure C); (b) the anisotropy in the local potentials in the subsystem of off‐centered B‐site cations gradually decreases upon BNiT doping and diminishes at x =0.50< x MPB (Figure D), where the A‐cation‐localized ETO1 mode shows a pronounced minimum in wavenumber (Figure C) indicating coupling processes within the A‐cation subsystem; and (c) at the MPB composition, the A‐BO 3 mode that corresponds to the quasi‐TO1(A 1 +E) excitation in PT‐based ceramics softens and broadens (Figure B), revealing coupling between the adjacent local dipoles at the A and B sites, that is, between the sublattices of off‐centered A‐site and B‐site cations, a phenomenon that appears to be universal for perovskite‐type ferroelectric solid solutions with MPB . All together, this indicates that at room temperature, the composition‐induced local‐scale rearrangements within the A‐cation subsystem as well as within the B‐cation subsystem occur slightly below the MPB, which probably facilitates the change of the ferroelectric long‐range order at the MPB.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially available PbTiO 3 powder from Sigma‐Aldrich with a purity of 99.9 % was used as a reference undoped material. The chemical compositions of the samples were verified by wavelength‐dispersive electron microprobe analysis using a Cameca Microbeam SX100 system . The room‐temperature unit‐cell parameters were derived from powder XRD patterns collected with a STOE STADI‐MP diffractometer in Bragg‐Brentano geometry over a 2 θ ‐range of 20° to 90°.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations